Genetic characterization of penicillin-binding proteins of nonencapsulated Streptococcus pneumoniae in the postpneumococcal conjugate vaccine era in Japan. (July 2022) - Kawaguchiya, Mitsuyo; Urushibara, Noriko; Aung, Meiji Soe; Kudo, Kenji; Ito, Masahiko; Habadera, Satoshi; Kobayashi, Nobumichi
Highlights: A total of 67.6% of nonencapsulated S. pneumoniae (NESp) were nonsusceptible to penicillin. Penicillin-binding proteins (PBPs) of 71 NESp isolates were genetically analyzed. To the best of our knowledge, all the PBP profiles (1a-2b-2x) that were identified were novel. NESp had more diverse mutations in PBPs than encapsulated S. pneumoniae . Various mutations in PBPs may be related to penicillin nonsusceptibility in NESp. Abstract: Objectives: Nonencapsulated Streptococcus pneumoniae (NESp) is emerging after the introduction of pneumococcal conjugate vaccines (PCVs). This study aimed to elucidate the genetic characteristics of penicillin-binding proteins (PBPs; PBP1a, 2b, and 2x) associated with penicillin nonsusceptibility in emergent NESp. Methods: A total of 71 NESp isolates that were identified in our previous study during the PCV era in Japan (2011–2019) were analyzed for their amino acid sequences of transpeptidase domain in PBP 1a, 2b, and 2x. Results: Overall, we identified 21 different PBP profiles (1a-2b-2x), all of which represent novel PBP profiles. The dominant PBP profiles were 13-16-ne1 (32.4%, n = 23), ne1-16-ne2 (14.1%, n = 10), and 13-7-ne4 (7.0%, n = 5) (novel PBP type was numbered with "ne" denoting "nonencapsulated"), accounting for 53.5% of all isolates. All isolates with the PBP profiles 13-16-ne1 and 13-7-ne4 and those having PBP1a type-13 and -131, PBP2b type-7, -ne1, and -ne2 showed nonsusceptibility to penicillin. A high degree of genetic diversity was found in PBP2x, with most of them (81.7%) being new types. Conclusions: Our current study identified the 21 novel PBP profiles and remarkable mutations in the PBPs, which may be potentially associated with penicillin nonsusceptibility in NESp.